2023
DOI: 10.1038/s41467-023-37610-w
|View full text |Cite
|
Sign up to set email alerts
|

Chance promoter activities illuminate the origins of eukaryotic intergenic transcriptions

Abstract: It is debated whether the pervasive intergenic transcription from eukaryotic genomes has functional significance or simply reflects the promiscuity of RNA polymerases. We approach this question by comparing chance promoter activities with the expression levels of intergenic regions in the model eukaryote Saccharomyces cerevisiae. We build a library of over 105 strains, each carrying a 120-nucleotide, chromosomally integrated, completely random sequence driving the potential transcription of a barcode. Quantify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In this study, we assumed that all genomic regions can potentially become a TFBS. This assumption is reasonable at least qualitatively, because “leaky expression” caused by fortuitous TF binding is indeed widespread, as evidenced by the observation that over three quarters of the human genome is transcribed ( Kellis et al 2014 ) and that about one half of 120-nucleotide random sequences can drive gene expression in yeast ( Xu et al 2023 ). However, if different genomic regions have different potentials to evolve into a TFBS in the focal lineage, method 2 could overcorrect the ascertainment bias when regions with low potentials are counted.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we assumed that all genomic regions can potentially become a TFBS. This assumption is reasonable at least qualitatively, because “leaky expression” caused by fortuitous TF binding is indeed widespread, as evidenced by the observation that over three quarters of the human genome is transcribed ( Kellis et al 2014 ) and that about one half of 120-nucleotide random sequences can drive gene expression in yeast ( Xu et al 2023 ). However, if different genomic regions have different potentials to evolve into a TFBS in the focal lineage, method 2 could overcorrect the ascertainment bias when regions with low potentials are counted.…”
Section: Discussionmentioning
confidence: 99%
“…Their numbers are broadly similar: although there are only −20,000 human lncRNA genes annotated in GENCODE 1 , −100,000 human lncRNA genes have been catalogued in dedicated databases (Fang et al, 2017;The RNAcentral Consortium, 2018;Ma et al, 2019;Volders et al, 2019;Statello et al, 2021); there are likely many more (Deveson et al, 2017), given the under sampling of cells at different developmental stages and the high resolution analyses that have revealed the existence of previously unreported lncRNAs and their isoforms expressed from GWAS regions (Bartonicek et al, 2017;Hardwick et al, 2019), across ch21 (Deveson et al, 2018) and from well-characterized loci, such as those containing p53 and HOX genes (Mercer et al, 2012). While some may be a product of transcriptional noise (Brosius and Raabe, 2016;Xu et al, 2023), thousands of lncRNAs (including many "antisense" RNAs) have been shown to have biological effects when their sequence or expression is perturbed and, while most have not been investigated, indices of their functionality include differential expression, subcellular localization, promoter and splice site conservation, multiexonic structure and extensive alternative splicing (Mattick and Amaral, 2022;Mattick et al, 2023), the latter shown to affect enhancer activity (Tan and Marques, 2022). Like lncRNAs generally (although there are exceptions, such as lncRNAs associated with more generic subnuclear domains such as nucleoli, paraspeckles and neuronal granules Yamazaki and Hirose, 2021;Grzejda et al, 2022)), elncRNAs are expressed at relatively low levels and exhibit only modest conservation across species (Deveson et al, 2017;Sartorelli and Lauberth, 2020;Mattick et al, 2023), features consistent with cell-and lineage-specific regulatory functions.…”
Section: Transcription From Enhancersmentioning
confidence: 99%
“…The biological interpretation of nORF expression is complex. Some studies suggest that the transcription or translation of nORFs could be attributed to expression noise [ 30 32 ], whereby non-specific binding of RNA polymerases and ribosomes to DNA and RNA might cause promiscuous transcription or translation, respectively. How do nORFs become expressed in the first place?…”
Section: Introductionmentioning
confidence: 99%